A Broken Social Contract, Not High Inequality, Led to the Arab Spring. (20th February 2017) - Devarajan, Shantayanan; Ianchovichina, Elena
Abstract : During the 2000s, expenditure inequality in Arab countries was low or moderate and, in many cases, declining. Different measures of wealth inequality were also lower than elsewhere. Yet, there were revolutions in four countries and protests in several others. We explain this so‐called "inequality puzzle" by first noting that, despite favorable income inequality measures, subjective well‐being measures in Arab countries were relatively low and falling sharply, especially for the middle class, and in the countries where the uprisings were most intense. The increasing unhappiness, reflected in perceptions of declining standards of living, was associated with dissatisfaction with the quality of public services, the shortage of formal‐sector jobs, and corruption. These sources of dissatisfaction suggest that the old social contract, where government provided jobs, free education and health, and subsidized food and fuel, in return for the subdued voice of the population, was broken. The Arab Spring and its aftermath indicates the need for a new social contract, one where government promotes private‐sector jobs and accountability in service delivery, and citizens are active participants in the economy and society.